The experiences of work family issues amongst women entrepreneurs in Lesotho - Motsomotso, Maletlatso (University of the Free State, 2021)
Women in Lesotho are increasingly becoming empowered and this is proven by the increase in the number of women opening and managing small businesses. On the other hand, societal expectations in Lesotho place household and childcare responsibilities on women. This becomes a challenge of balancing the work and family issues of women who own businesses in Lesotho. The challenges, causes as well as the effects of work family issues on the success of businesses owned by women have been studied, offering substantial knowledge to researchers about women entrepreneurs and their businesses. However, there is limited research on the impact of work family issues and how they affect the success of women in business therefore, more studies need to be conducted in countries such as Lesotho. Given that family has a huge influence on women entrepreneurs, the success or failure of their businesses may occur when there is an imbalance of work family issues (i.e. work family conflict, work family enrichment, and family support). This study primarily aimed to assess the experiences of work family issues and the impact they have on the success of women who own businesses in Lesotho. This study argues that knowledge about the intricacies of how the family and work domains interact for women entrepreneurs in Lesotho is still very scarce. Therefore, examining in-depth the experiences of women entrepreneurs in Lesotho, the present study did not only enhance the existing literature by providing evidence from a new context but also unearthed some of these intricacies to show how support, enrichment, and conflict co-exist. The findings of the study are vital in shedding light on how to improve the success of women who own businesses in Lesotho and other developing and developed countries. This is particularly important as empowering women entrepreneurs and enhancing their success is important for sustainable economic development. A qualitative research method was used to study the experiences of work family issues and how they affect the success of women entrepreneurs in Lesotho. 30 in-depth semi structured interviews were used to collect data from women who own businesses in the three districts of Lesotho (Leribe, Maseru, and Mafeteng). Results of this study showed that: • Women entrepreneurs established their businesses because of the push, pull, and mixed factors. The pull factors included: passion, family background and role models, low cost of entry, and copreneurship. Push factors included: hunger and poverty reduction and unemployment while autonomy was the only mixed factor identified. • Women entrepreneurs experienced all three types of conflict (i.e. time based, strain based, and behaviour based) from their families and businesses. The time based conflict in the work domain was experienced through long working hours while the time based conflict in the family domain was caused by household work. With the strain based conflict, women struggled to fulfill household responsibilities due to fatigue caused by the workload in their businesses. The behaviour based conflict was characterised by trust issues that developed in the business. There was a lack of trust that women entrepreneurs developed in their businesses which affected their families as they could no longer trust their families on anything. As a result, this could lead to conflict in their families. • Findings on the consequences of work-to-family/family-to-work conflict revealed that the family activities of women entrepreneurs led to negative relationships with their families. In the work domain, the work responsibilities of women who own businesses negatively affected their relationships with their employees, led to the loss of income in their businesses, resulted in a decrease in productivity levels in their businesses, and also resulted in business exit intentions. • The challenges that women entrepreneurs in Lesotho encountered included: business expense, employee theft, and competitive strategy as well as credit sale strategies. • Women entrepreneurs experienced both the instrumental and the affective work family enrichment from their families and businesses. Instrumental enrichment in the work domain was experienced through gaining patience, decision making abilities, creativity, and humility. In the family domain, instrumental enrichment was characterised by creativity which women entrepreneurs used to improve their businesses. Looking at the affective enrichment, happiness experienced in the business enabled women to portray happiness in their families as well. Looking at the consequences of work-to-family/family-to-work enrichment, being in business resulted in the organisational commitment of women entrepreneurs. • Women entrepreneurs received different types of support (i.e. financial and non-financial, emotional and instrumental) from their families and friends. • The work life balance strategies that women entrepreneurs used were grouped into segmentation, integration, and mixed work life balance strategies. The integration strategies consisted of communication and work flexibility while household management was the only segmentation strategy used. The mixed work life balance strategies include delegating and time management. • The factors of success identified by women entrepreneurs included hardwork and financial literacy. The perceptions of success in women entrepreneurs include growth, satisfaction, financial performance, and provision of family or community needs. Moreover, this study makes the following recommendations: • First of all, participants in this study experienced employee theft. Therefore, this study recommends that policies have to be put in place that would help regulate and reduce the effect of employee theft on businesses. • Business expenses were also found to negatively affect success and the family. As a result, women entrepreneurs can opt to operate their businesses from home to reduce operating costs which include the cost of traveling to work, office rent, and other costs related to non-home-based business. • Moreover, women entrepreneurs also had trust issues that developed in their businesses and were transferred into their families. As a result, this study recommends that entrepreneurs in Lesotho learn to effectively separate the behaviour portrayed in business from the behaviour portrayed in their families. The issues that arise in one domain (business) must be left in business and not be carried over into another domain (family). • Participants in this study struggled to recover from the fatigue they experienced from their businesses which made it difficult for them to handle their children. Therefore, this study recommends that women entrepreneurs in Lesotho practice self-care habits such as taking naps after work to regain their strength so that they can give their children the attention they need. Getting enough sleep will uplift their mood, increased creativity, and productivity levels which will lead to the success of their businesses.
Thesis (Ph.D. (Business Managment))--University of the Free State, 2021
Keywords: Work family conflict; Work family enrichment; Family support; Work life balance; Success; Women entrepreneurs; Lesotho